Assessment of genetic variability parameters and trait association in chilli (Capsicum annuum L.) - Sharma , D; Shailja; Nikhil , T; Jasdeep , K; Diksha, S (Plant Science Today, 2025)
A study conducted during the 2022–2023 season evaluated 15 chilli genotypes, including one check variety, to identify those with superior yield and quality traits. The genotypes exhibited significant genetic variability, indicating broad genetic diversity across morphological and yield parameters. Traits such as fruit width (98.77 %), ascorbic acid content (99.83 %), and fruits per plant (99.83 %) showed high heritability and genetic advance, underscoring the predominance of additive genetic effects and highlighting their potential for improvement through selection. Correlation analysis revealed strong positive associations between fruit yield per plot and traits such as fruit weight (0.805 and 0.711), fruit length (0.593 and 0.462), and fruit width (0.676 and 0.572), emphasizing their collective contribution to yield. Path coefficient analysis showed significant direct effects of traits like fruit width, fruit weight, and hundred seed weight on fruit yield. Additionally, principal component analysis (PCA) revealed that the first component was the most influential in explaining the variance. This study stands out by providing detailed insights into the genetic variability of chilli genotypes, offering a more comprehensive understanding compared to previous research. These findings have essential breeding implications, specifically recommending that breeders focus on traits with high heritability and genetic advance, such as fruit width, fruit weight, and ascorbic acid content, to enhance yield and quality. Breeding programs should prioritize these traits for selection to develop high-yielding, nutrient-rich chilli cultivars with improved resilience and consistency. This approach will help accelerate the development of improved chilli varieties, benefiting both commercial production and consumer health.